2021
DOI: 10.1186/s12884-021-04252-z
|View full text |Cite
|
Sign up to set email alerts
|

Infant crying problems related to maternal depressive and anxiety symptoms during pregnancy: a prospective cohort study

Abstract: Background Infant crying may cause concerns among new parents and is a frequent reason for seeking help from their general practitioner (GP). The etiology of crying problems in infancy is not fully understood, but recent studies have found associations with maternal mental factors. It is well-established that postpartum depression is related to infant crying problems while the influence of maternal mental problems in pregnancy on infant crying is less investigated. We aimed to explore whether m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…Several studies have shown that mental issues during pregnancy are associated with an increased risk of having a child with IC after birth. 3 , 4 , 24 Increased psychological distress during the pandemic in pregnant women 14 could have resulted in more infants with IC. This could explain the increase in our study in the number of “excessive crying” diagnoses compared to the stable numbers of total paediatric diagnoses pre‐ and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that mental issues during pregnancy are associated with an increased risk of having a child with IC after birth. 3 , 4 , 24 Increased psychological distress during the pandemic in pregnant women 14 could have resulted in more infants with IC. This could explain the increase in our study in the number of “excessive crying” diagnoses compared to the stable numbers of total paediatric diagnoses pre‐ and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of parental psychopathology are a risk factor for early child development. Maternal symptoms of depression and anxiety are among the strongest predictors of child regulatory problems and externalizing symptoms (Reinelt et al., 2019 ; Ölmestig et al., 2021 ). In addition, higher parental stress levels can affect child development via parental investment and parenting behavior (Bradley et al., 1997 ; Neppl et al., 2016 ).…”
Section: Parental Well‐being and Parenting During The Pandemicmentioning
confidence: 99%
“…A mental health related measure needs to be well developed and thoroughly validated, with clear definition and scope, to ensure clarity of findings, meaningful interpretation and reproducibility. This Collection includes large and small scale studies, cross-sectional studies [5,16,11], cohort studies [18,22] and studies validating new screening or measurement tools [8,13,17].…”
Section: Rationale For This Collectionmentioning
confidence: 99%
“…Where factors were identified which predict poorer perinatal mental health, these were commonly associated with disadvantage and limited access to resources. Associations with possible predictors, including pregnancy acceptability [34], self-care [35], childhood trauma [36], alcohol and substance misuse [36] and infant crying [22] were explored. Other demographic and individual characteristics were recognised by some researchers as key in understanding some of the associations with poor, positive or improved mental health.…”
Section: Incidence Determinants and Factors Associated With Poor And ...mentioning
confidence: 99%